Stabilization of the air-liquid interface in sponge cake batter by surface-active proteins and lipids: A foaming protocol based approach. (April 2020) - Pycarelle, Sarah C.; Bosmans, Geertrui M.; Nys, Hélène; Brijs, Kristof; Delcour, Jan A.
Abstract: The presence of protein and lipid from wheat flour and eggs at the air-liquid interface (ALI) in sponge cake batter has been studied through a foaming protocol. Sponge cake batter was either prepared from flour, sugar, eggs and leavening agents only or from these ingredients and exogenous lipids (ELs, i.e. a combination of mono- and diacylglycerols and polyglycerol esters of fatty acids). The foaming protocol consisted of whipping diluted sponge cake batter into foam. The foam was considered to be a model for the ALI in sponge cake batter. Foam fractions were then isolated at multiple time points after whipping and chemically analyzed ( i.e. lipid and proteins contents and their compositions). In absence of ELs, lipids were not enriched in the foam whereas proteins were. Under such conditions, proteins were more important for stabilizing the ALI than lipids. Size-exclusion high performance liquid chromatography profiles revealed that of all proteins in the system ovalbumin and wheat α- and γ-gliadins had the highest affinity for the ALI. Ovalbumin molecules unfolded and formed intermolecular disulfide bonds at the ALI. Furthermore, flour lipids had higher affinity for the ALI than egg lipids. When ELs were used, foam protein and lipid content and composition essentially remained constant over the experimental time period. In such case, they dominated the ALI and greatly contributed to its stability. Use of ELs decreased batter density and increased batter viscosity, cake volume and cake softness. Hence, it is clear that including ELs in the sponge cake recipe led to high batter and cake quality. Graphical abstract: Image 101108 Highlights: Proteins stabilize gas cells in sponge cake batter more than wheat and egg lipids. Proteins form intermolecular disulfide bonds at the interface in sponge cake batter. Ovalbumin and α- and γ-gliadins have high affinity for the interface in the batter. When used, exogenous lipids dominate the interface in the batter.